Sperm and sex peptide stimulate aggression in female Drosophila - Bath,E; Bowden,S; Peters,C; Reddy,A; Tobias,JA; Easton-Calabria,E; Seddon,N; Goodwin,SF; Wigby,S (Nature Ecology and Evolution, 2017)
Female aggression towards other females is associated with reproduction in many taxa, and traditionally thought to be related to the protection or provisioning of offspring, such as through increased resource acquisition. However, the underlying reproductive factors causing aggressive behaviour in females remain unknown. Here we show that female aggression in the fruit fly Drosophila melanogaster is strongly stimulated by the receipt of sperm at mating, and in part by an associated seminal fluid protein, the sex peptide. We further show that the post-mating increase in female aggression is decoupled from the costs of egg production and from post-mating decreases in sexual receptivity. Our results suggest that male ejaculates can have a surprisingly direct influence on aggression in recipient females. Male ejaculate traits thus influence the female social competitive environment with potentially far-reaching ecological and evolutionary consequences.